The 7 Habits of Highly Effective People - Covey, Stephen R. (London Simon & Schuster, 1999)
A leading management consultant outlines seven organizational rules for improving effectiveness and increasing productivity at work and at home.
Include Tables and Index
Keywords: Success--Psychological aspects -- Character -- Self-actualization (Psychology)